THE PRACTICE OF DIALOGUES IN THE CLASSROOM: A CONDITION FOR THE STUDENTS’ MATHEMATICAL CONCEPTUAL ELABORATION - Juliana Bagne; Adair Mendes Nacarato (Reflexão & Ação, 2012)
This article refers to an excerpt from a Master research based on a qualitative approach with students from the 2nd year of Primary School at a municipal school in Jundiaí/SP and has as its focus problem posing in the classroom. Aiming to analyse the mathematical conceptual elaboration carried out by students inserted in a problem-based environment as well as the mediation attitudes taken by the teacher-researcher within this context, the chosen theoretical reference is the historical-cultural perspective. The excerpt here presented refers to the analysis of one of the seven episodes chosen for the research and focuses on the conceptual elaboration in the classroom, with emphasis on the production of meanings for the concept of length measurement. The results reveal how often students bring mathematical meanings related to non-school contexts involving measurements and how these spontaneous concepts allow for the access to scientific concepts, in a movement of argumentation, socialization, interaction and mediated actions.